RAGAM BAHASA DALAM KISAH INSPIRATIF INDONESIA MENGAJAR - Berliana Singamou, Intan; Isani Kulup, Luluk Isani Kulup (Universitas PGRI Adi Buana Surabaya, 2019)
This research is motivated by the diversity or kevariasian language contained in a region. As a tool for expressing thoughts and feelings, the choice of language varieties largely determines what the audience is saying is understood or not. In the Inspirational story of Indonesia teaching, there are people who have more than one language, and speakers also come from unequal regions or regions, so speakers have to choose exactly which languages to use. The purpose of this study is to describe the variation of language in the Indonesian Inspirational story of teaching. This research uses qualitative approach with description method. Data collection techniques used in this study is documentation. Then, the data is analyzed in accordance with the existing procedure. The object of this research is the utterance or speech of the characters in the story Inspiratif Indonesia teaching. The results of this study indicate that, in speaking or communicating, the characters or speakers in the Indonesian Inspirational taught to choose or use a variety of language based on situations, speech partners, habits, and age, so they tend to use non-formal language variety in saying or communicating. The variety of languages used in the Indonesian Inspirational story teaching is a variety of business or consultative variety, casual or casual variety, intimate or intimate variety, literature, and literary variety.